Effect of dimethyl sulfoxide on dentin collagen. Issue 8 (August 2017) - Mehtälä, P.; Pashley, D.H.; Tjäderhane, L.
Graphical abstract: Highlights: Pretreatment of demineralized dentin with 1–5% DMSO increases wettability. DMSO has a concentration-dependent effect on dentin matrix expansion/shrinkage. The effects may relate to DMSO's ability to change water behavior in dentin matrix. Abstract: Objectives: Infiltration of adhesive on dentin matrix depends on interaction of surface and adhesive. Interaction depends on dentin wettability, which can be enhanced either by increasing dentin surface energy or lowering the surface energy of adhesive. The objective was to examine the effect of dimethyl sulfoxide (DMSO) on demineralized dentin wettability and dentin organic matrix expansion. Methods: Acid-etched human dentin was used for sessile drop contact angle measurement to test surface wetting on 1–5% DMSO-treated demineralized dentin surface, and linear variable differential transformer (LVDT) to measure expansion/shrinkage of dentinal matrix. DMSO-water binary liquids were examined for surface tension changes through concentrations from 0 to 100% DMSO. Kruskal–Wallis and Mann–Whitney tests were used to test the differences in dentin wettability, expansion and shrinkage, and Spearman test to test the correlation between DMSO concentration and water surface tension. The level of significance was p < 0.05. Results: Pretreatment with 1–5% DMSO caused statistically significant concentration-dependent increase in wetting: the immediate contact angles decreased by 11.8% and 46.6% and 60 s contact angles by 9.5% and 47.4% with 1% and 5% DMSO, respectively. DMSO-water mixtures concentration-dependently expanded demineralized dentin samples less than pure water, except with high (≥80%) DMSO concentrations which expanded demineralized dentin more than water. Drying times of LVDT samples increased significantly with the use of DMSO. Significance: Increased dentin wettability may explain the previously demonstrated increase in adhesive penetration with DMSO-treated dentin, and together with the expansion of collagen matrix after drying may also explain previously observed increase in dentin adhesive bonding.